FACTORS THAT AFFECT WOMEN'S MOTIVATION TO ENTREPRENEURS IN PEKANBARU (CASE STUDY ON VILLA BUNGA ARENGKA RESIDANCE PEKANBARU) - Febrina, Dian (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
The entrepreneurship sector is one of the business fields which is the choice for women to prove their ability in entrepreneurship. This study aims to determine the motivation of women, especially housewives in entrepreneurship in Pekanbaru. The data used are primary and secondary data with qualitative descriptive methods. From the pre-survey conducted on housewives in Villa Bunga Arengka Residance, 27.5% of housewives are involved in entrepreneurship which mostly use online services in marketing their sales products. Independent variables used in this study are independence, capital, emotional and education. While the dependent variable in this study is entrepreneurial motivation of housewives. Data collection using online questionnaires and data analysis techniques using quantitative analysis techniques with multiple linear regression analysis tools.